Perception and Awareness Among Food Manufacturers and Marketers on Halal Food in the Klang Valley - Abdullah, Ahmad Nizam (2006)
The increasing demand for halal food that is USD 346.7 billion or equal to RM 1 317 billion annually is in tandem with the growth of Muslims population,better education level and higher purchasing power. With expanding global markets, innovative food companies are leading the charge by carving a new niche to gain competitive edge in the marketplace.The mission of Malaysian Government to position Malaysia as an International Halal Food Hub sets the country on a strategic route to be the main halal food supply base and global halal certification centre. As a highly reputed, moderate and progressive Islamic country with more than 3,500 food manufacturing companies and total output exceeding USD 9 billion, Malaysia is well poised to play a leading role in boosting the halal food market.This study attempts to look at the perceptions and awareness among food manufacturers and marketers on halal food including halal food hub and government grant or incentives with regards to halal food.The data for this research were collected from 90 food manufacturers and marketers operating in Klang Valley.The findings indicate that 69 percent of food companies that obtained halal certification from JAKIM are still lacking initiative to appoint halal food committees in their organization.In addition, they do not refer to any halal authority before purchasing any unconventional raw materials.The food manufacturer’s and marketers perception on grant or incentive for halal food purposes showed more than 70 percent of the food manufacturers and marketers agreed that grant or incentive provided by the government can helps to develop halal food industry in Malaysia.This study also revealed that 61.1 percent of the companies in food industry do not get any grant or incentives from any government agencies.This situation was due to lack of promotions and information about grant or incentives offered to the food company involved in halal food industry.The same statistical analysis was used to determine the food manufacturers’and marketers perceptions of Malaysia as halal food hub. A total of 40 percent of the respondents think that Malaysia is able to become halal foodhub of the world. This low figure showed that there are weak coordination among government agencies in Malaysia and poor support from the private sector to materialise the concept of halal food hub. The study showed that the awareness regarding halal food [perception on halal label (Pearson Chi-Square, 0.029) and the need to have halal food act (Pearson Chi-Square, 0.009)]are found to be significantly related to the company’s annual sales turnover with level of confidence at 95 percent (α = 0.05). The study also showed those food manufacturers’ and marketers’ perception of Malaysia as a halal food hub is not influenced by the companies’ annual sales turnover.This study indicates that most of food manufacturers and marketers in Klang Valley are perplex with regards to the initiative to appoint internal halal food committee and referring to halal authority before purchasing unconventional raw materials. Although there are many cases of fake and misused halal logo in Malaysia,most of the food manufacturers and marketers in Klang Valley still have deep awareness and good perception towards halal food matters.Therefore,Malaysian government should take this opportunity as a yardstick to measure the effectiveness of government policies regarding halal food matters including educating Malaysian food manufacturers and marketers and promoting attractive grant or incentives specifically for halal food businesses. This is important to increase Malaysian halal food industry competitiveness in the global market and to position Malaysia as a Global Halal Food Hub.